Identification and validation of reference genes for RT-qPCR analysis in Iris domestica under Cd stress - Beibei Su; Ziwei Li; Hongli Liu; Xiaoyun Niu; Xiaojie Zhao; Yumeng Wu; Qian Wang; Yangchen Yuan; Zhuolin Xiao; Dazhuang Huang (Heliyon, 2024)
Iris domestica is a widely used ornamental garden and important medicinal plant. Our previous studies have shown that it exhibits significant uptake and translocation capacity under Cd stress compared to other Iris species. Gene expression is studied using RT-qPCR; however, there are no reference genes have been found for I. domestica under Cd stress. In this investigation, thirteen possible reference genes from previous studies and our transcriptome were screened using RT-qPCR in the leaves and roots of Cd-stressed plants. The findings revealed that UBC9 and ACT were the best reference genes for roots with and without Cd stress, whereas YLS8 and ACT7 were the best reference genes for leaves. Among the different tissues without Cd stress, UBC9 and UBC28 exhibited the best results, whereas PP2C06 and UBC9 exhibited the best results under Cd stress. The most stable reference genes in the leaves and roots were UBC9 and UBC28, respectively, under and without Cd stress, and GADPH was the most unstable. Finally, three metal ion response genes, NRAMP2, YSL9 and CYP81Q32 were detected using RT-qPCR and compared with the transcriptome data to further confirm the reliability of the chosen genes. This study identified suitable reference genes for I. domestica under Cd-stress conditions.